Crystal structure of 1-{3-(4-methylphenyl)-5-[(E)-2-phenylethenyl]-4,5-dihydro-1H-pyrazol-1-yl}ethan-1-one - Adam, Farook; Smitha, Kanathur; Poojary Charishma, Sharath; Samshuddin, Seranthimata; Ameram, Nadiah (International Union of Crystallography, 2015)
The title compound, C20H20N2O, was studied as a part of our work on pyrazoline derivatives. It represents a trans-isomer. The central pyrazoline ring adopts an envelope conformation with the asymmetric C atom having the largest deviation of 0.107 (1) A ° from the mean plane. It forms dihedral angles of 6.2 (1) and 86.4 (1) with the adjacent p-tolyl and styrene groups, respectively. In the crystal, C—H O interactions link molecules into infinite chains along the c axis.